Impact of Pretransplant Malignancy on Heart Transplantation Outcomes: Contemporary United Network for Organ Sharing Analysis Amidst Evolving Cancer Therapies. (31st January 2022) - Batra, Jaya; DeFilippis, Ersilia M.; Golob, Stephanie; Clerkin, Kevin; Topkara, Veli K.; Habal, Marlena V.; Restaino, Susan; Griffin, Jan; Hi Lee, Sun; Latif, Farhana; Farr, Maryjane A.; Sayer, Gabriel; et al.
Abstract : Background: An aging population and improved cancer survivorship have increased the number of individuals with treated malignancy who develop advanced heart failure. The benefits of heart transplantation (HT) in patients with a pretransplant malignancy (PTM) must be balanced against risks of posttransplant malignancy in the setting of immunosuppression. Methods: Adult patients in the United Network for Organ Sharing registry who received HT between January 1, 2010, and December 31, 2020 were included. Trends, patient characteristics, and posttransplant outcomes in HT recipients with PTM were evaluated. Results: From 2000 to 2020, the proportion of HT recipients with PTM increased from 3.2% to 8.2%. From 2010 to 2020, 2113 (7.7%) of 27 344 HT recipients had PTM. PTM was associated with higher rates of 1-year mortality after HT (11.9% versus 9.2%; adjusted hazard ratio, 1.25 [95% CI, 1.09–1.44], P =0.001), driven by increased mortality in patients with hematologic PTM (adjusted hazard ratio, 2.00 [95% CI, 1.61–2.48]; P <0.001). For recipients who survived the first year, 5-year survival was similar between patients with and without PTM. Rates of malignancy at 5-years posttransplant were higher in the PTM group (20.4% versus 13.1%; adjusted hazard ratio, 1.57 [95% CI, 1.38–1.79], P <0.001). Conclusions: Prevalence of PTM in HT recipients nearly tripled over the past 2 decades. Patients with hematologic PTM were at increased risk of early mortality after HT. Patients with PTM were also at higher risk for posttransplant malignancy. Guidelines that reflect contemporary oncological care are needed to inform care of this heterogenous and expanding group of individuals.